WAYS TO ENHANCE THE ENDURANCE OF ADOLESCENT ATHLETES IN SWIMMING TRAINING - Xalmatova Nasiba Bozarboyevna (Research Focus International Scientific Journal, 2025)
This article analyzes effective methods for developing and enhancing endurance in adolescent swimmers. Endurance plays a key role in athletes’ technical and tactical preparation, contributing significantly to successful performance in competitions. The study explores the optimal organization of load and rest ratios in swimming training, the balance between aerobic and anaerobic exercises, as well as the influence of motivation and psychological readiness on endurance.